Vitamin B-12 status during pregnancy and child's IQ at age 8: a Mendelian randomization study in the Avon longitudinal study of parents and children. - Carolina Bonilla; Debbie A Lawlor; Amy E Taylor; David J Gunnell; Yoav Ben-Shlomo; Andrew R Ness; Nicholas J Timpson; Beate St Pourcain; Susan M Ring; Pauline M Emmett; A David Smith; Helga Refsum; et al. (PLoS ONE)
Vitamin B-12 is essential for the development and maintenance of a healthy nervous system. Brain development occurs primarily in utero and early infancy, but the role of maternal vitamin B-12 status during pregnancy on offspring cognitive function is unclear. In this study we assessed the effect of vitamin B-12 status in well-nourished pregnant women on the cognitive ability of their offspring in a UK birth cohort (ALSPAC). We then examined the association of SNPs in maternal genes FUT2 (rs492602) and TCN2 (rs1801198, rs9606756) that are related to plasma vitamin B-12, with offspring IQ. Observationally, there was a positive association between maternal vitamin B-12 intake and child's IQ that was markedly attenuated after adjustment for potential confounders (mean difference in offspring IQ score per doubling of maternal B-12 intake, before adjustment: 2.0 (95% CI 1.3, 2.8); after adjustment: 0.7 (95% CI -0.04, 1.4)). Maternal FUT2 was weakly associated with offspring IQ: mean difference in IQ per allele was 0.9 (95% CI 0.1, 1.6). The expected effect of maternal vitamin B-12 on offspring IQ, given the relationships between SNPs and vitamin B-12, and SNPs and IQ was consistent with the observational result. Our findings suggest that maternal vitamin B-12 may not have an important effect on offspring cognitive ability. However, further examination of this issue is warranted.